Modulating the Dissolution and Mechanical Properties of Resveratrol by Cocrystallization - He, Hongyan; Zhang, Qi; Li, Meiqi; Wang, Jian-Rong; Mei, Xuefeng (Crystal growth & design, 2017)
Resveratrol (RSV), a dietary polyphenol found in red wine, has renewed interest in recent years due to a broad range of in vitro evidence that indicate cardioprotective effects. Herein, we have synthesized four RSV cocrystals with the objective to improve the physicochemical and mechanical properties. Single crystal structures were illustrated and comprehensive characterization of the cocrystals were performed. In addition, powder dissolution of RSV cocrystals in different buffer medium containing different surfactants were conducted, and the result revealed that PVP K30 is an effective surfactant to maintain the supersaturation. Then pharmacokinetic experiments suggested that RSV cocrystals showed shorter T max, and RSV–NA exhibited higher C max and AUC0–24 values. Furthermore, RSV cocrystals exhibited superior mechanical properties compared to RSV pure component. These results may provide an alternative formulation for RSV.